O-087 Asthma and allergies in a cohort of adolescents conceived after assisted reproductive technologies (ART). (30th June 2022) - Wijs, L; Doherty, D A; Keelan, J A; Penova-Veselinovic, B; Burton, P; Yovich, J L; Hall, G L; Sly, P D; Holt, P G; Hart, R J
Abstract: Study question: Are adolescents conceived after assisted reproductive technologies (ART) at an increased risk of asthma and allergies, compared to their counterparts conceived without ART? Summary answer: No difference in asthma prevalence, better lung-function, and an increase in allergic rhinoconjunctivitis, food allergies and positive skin-prick tests are reported in the ART cohort. What is known already: Over 8 million children have been born after conception with ART worldwide. Emerging evidence shows an increased risk of atopic disorders, such as asthma and allergies, in such children, potentially due to epigenetic alterations or underlying parental subfertility and perinatal risk factors. Studies to date are highly heterogeneous, including non-standardized diagnostic tools, non-representative reference populations, and lacking appropriate covariate adjustment. With the increase in atopic disorders worldwide, and the burden they bring to the life of individuals and to society, in combination with the increase in ART, it is important to further investigate the risk of atopy in such offspring. Study design, size, duration: The Growing Up Healthy Study (GUHS) is a prospective study that recruited 303 offspring conceived after ART (aged 13-21), born 1991-2001 in Western Australia. Their health parameters, including asthma and allergy assessments, were compared with those of counterparts conceived without ART, from the Raine Study Generation 2 (Gen2). The 2, 868 Gen2 participants are representative of the local population. At age 14 (2013-2017), 152 GUHS participants replicated atopy assessments previously completed by similarly aged Gen2 participants. Participants/materials, setting, methods: Asthma and allergy assessments consisted of a parent-completed modified version of the 'International Studies of Asthma and Allergies in Childhood' (ISAAC) questionnaire, spirometry, methacholine challenge- and skin-prick testing (SPT). Chi 2, Fisher's Exact and Mann-Whitney U tests, performed in SPSS V25, examined cohort differences, and generalized estimating equations adjusted for (a subset of) the following covariates: sex, age, height, singleton pregnancy, gestational age, birthweight, mode of delivery, primary caregiver smoking, and being an only child. Main results and the role of chance: Current asthma and asthma severity, based on the ISAAC questionnaire, appeared similar between the cohorts. Lung function (mean Forced Expiratory Volume [FEV1], Forced Vital Capacity [FVC] and FEV1/FVC ratio) was better in the ART cohort (3.10 vs. 2.96 L, p = 0.011; 3.72 vs. 3.29 L, p < 0.001; 85.5 vs. 91.8%, p < 0.001, respectively). No difference in mean Forced Expiratory Flow was reported. Bronchial hyperresponsiveness was significantly less prevalent in the ART cohort (8.8% vs. 18.6% p = 0.006). Current allergic rhinoconjunctivitis (ARC) rates were significantly higher in the ART cohort (32.4% vs. 25.2%, aOR 1.52 [1.03-2.26], p = 0.036), while prevalence of current atopic dermatitis did not differ. Food allergies were twice as prevalent in the ART cohort (20.7 vs. 10.9%, aOR 1.89 [1.17-3.06], p = 0.010). Significantly more GUHS participants had a positive SPT (68.0% vs . 45.4%, aOR 3.034 [1.989-4.628], p < 0.001). The percentage of polysensitisation (> 1 allergen) did not differ between the cohorts. Sub-analyses comparing offspring conceived after in vitro fertilisation (IVF)[n = 100] and intracytoplasmic sperm injection (ICSI)[n = 40], and fresh and frozen embryo transfers (ETs n = 82, FETs n = 58) within the ART cohort, showed no significant differences, although all allergy outcomes appeared more prevalent in the ET group. Limitations, reasons for caution: Despite substantial study size, numbers did not allow for adjustment for all covariates. Sub-analyses (IVF vs. ICSI and ET vs. FET), were conducted with limited power and require replication in larger cohorts. Both cohorts were largely of Caucasian decent (>88.0%), which reduces applicability of findings to other ethnicities. Wider implications of the findings: Reassuringly, adolescents conceived after ART had better lung-function than their counterparts and no differences in asthma prevalence. The reported increase in allergies in ART conceived adolescents is of importance to families and healthcare providers, and opens possibilities for targeted screening and treatment. Further studies are required to confirm our findings. Trial registration number: Not applicable